Prognostic Value of Preoperative Hemoglobin Levels for Long-Term Outcomes of Acute Type B Aortic Dissection Post-thoracic Endovascular Aortic Repair - Gao, Zhichun; Qin, Zhexue; An, Zhixia; Hou, Changchun; Wang, Luyu; Jin, Jun (Frontiers in Cardiovascular Medicine, 2020)
Background and Aims: There is scant information available about the prognostic value of preoperative hemoglobin (Hb) levels on the long-term outcomes of acute type B aortic dissection (ABAD) following thoracic endovascular aortic repair (TEVAR). Methods: A retrospective analysis of consecutive patients from 2010 to 2018 regarding the relationship between Hb level and long-term outcomes was conducted. The primary endpoint was all-cause mortality. Major adverse cardiovascular events (MACEs) included all-cause death, recurrent ruptures, and secondary procedures. Results: In total, 391 subjects treated by TEVAR were enrolled, with a mean age of 57.1 ± 12.0 years; 79.5% of them were male. Cox multivariate analysis showed that the preoperative Hb level was independently associated with all-cause death [adjusted hazard ratio (HR) 0.797 (per 1 g/dl), 95% confidence interval (CI) 0.693–0.918, p = 0.002] and MACEs (adjusted HR 0.795, 95% CI 0.672–0.871, p = 0.000). The area under the receiver operating characteristic curve of Hb for all-cause death and MACEs were 0.617 (95% CI 0.548–0.687, p = 0.008) and 0.617 (95% CI 0.551–0.684, p = 0.005), respectively. In the linear trend test, Hb concentration was significantly related to all-cause mortality (p for trend = 0.001) and MACEs (p for trend = 0.000). Moreover, in Kaplan–Meier analysis, lower Hb levels (< 12 g/dl) were significantly different from higher Hb (≥12 g/dl) levels for both all-cause death (log-rank p = 0.001) and MACEs (log-rank p = 0.001). Similar results were found when assessing the prognostic value of red blood cell count and anemia. Conclusions: Preoperative Hb may serve as a prognostic marker for long-range adverse outcomes for ABAD patients post-TEVAR.